Pola Pengobatan Antidiabetik Oral pada Pasien Diabetes Mellitus Tipe 2 Rawat Jalan di RSUD Kajen Pekalongan - Ainun Muthoharoh; Wiga Arum Safitri; Dwi Bagus Pambudi; Fadila Rahman (Pharmacon: Jurnal Farmasi Indonesia)
Diabetes mellitus is a chronic disease with long-term and routine treatment therapy. Combined or single oral antidiabetic therapy is given to be able to get normal and controlled blood sugar levels every month. The purpose of this study was to determine the treatment patterns in patients with type 2 diabetes mellitus outpatient at Kajen Regional Hospital in Pekalongan Regency. This study used an observational cross sectional approach which was conducted retrospectively. A total of 97 samples were taken from the medical records of type 2 diabetes mellitus patients who received oral antidiabetic drug therapy, who had routine medical treatment for 3 consecutive months in the Outpatient Installation of Kajen Regional Hospital in Pekalongan Regency for the period January-December 2017. Data analysis was conducted descriptively. The results of this study that patients with uncomplicated diabetes mellitus receive the most oral antidiabetic drugs with metformin, patients with diabetes mellitus with the most complications receive oral antidiabetic drugs pioglitazone and acarbose, and the type of drugs other than oral antidiabetics is aspilet. The need for special assessment of individual doses in patients with diabetes mellitus without or with pharmacokinetic and pharmacogenomic perspective complications